2009
DOI: 10.1111/j.1369-7625.2009.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Getting ready for user involvement in a systematic review

Abstract: Objective This paper aims to support the critical development of user involvement in systematic reviews by explaining some of the theoretical, ethical and practical issues entailed in Ôgetting readyÕ for user involvement.Background Relatively few health or social care systematic reviews have actively involved service users. Evidence from other research contexts shows that user involvement can have benefits in terms of improved quality and outcomes, hence there is a need to test out different approaches in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 20 publications
(30 reference statements)
0
58
0
1
Order By: Relevance
“…A total of 744 documents were identified in the search, discounting duplicates. Of these 744 documents, three papers were identified on public involvement in the systematic review process on the basis of paper title and abstract (where available) [20,21,25]. The two main reasons for exclusion were: (1) the document was not a systematic review or a reflection on the public involvement within an individual systematic review and (2) (for systematic reviews) no evidence was reported of the involvement of the public in the systematic review.…”
Section: Identifying Relevant Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…A total of 744 documents were identified in the search, discounting duplicates. Of these 744 documents, three papers were identified on public involvement in the systematic review process on the basis of paper title and abstract (where available) [20,21,25]. The two main reasons for exclusion were: (1) the document was not a systematic review or a reflection on the public involvement within an individual systematic review and (2) (for systematic reviews) no evidence was reported of the involvement of the public in the systematic review.…”
Section: Identifying Relevant Evidencementioning
confidence: 99%
“…Despite these surveys and aggregated accounts of public involvement within Cochrane review groups, detailed accounts of public involvement within individual systematic reviews in the fields of health and social care remain scarce [20,21]. The purpose of the present paper therefore is: to identify and review case examples of public involvement in the design and conduct of individual systematic reviews; to examine the methods, levels and stages of involvement reported; to synthesise the impacts of involving the public; to discuss the tensions, facilitating strategies and recommendations for good practice that have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…93 The benefits of PPI include enhanced depth, credibility and applicability of findings, improved clarity of final reports and recommendations and an immediate link between practice-based evidence and evidence-based methodology. [94][95][96] Although it is recognised that PPI in research should begin at the earliest stage possible, in practice it is not easily achievable. Constraints on time, funding, ethics approvals and the availability of appropriate representatives often mean that PPI is not included until research is fairly well advanced.…”
Section: Introductionmentioning
confidence: 99%
“…Ez a primer kutatásoknál is megköve-telt előfeltétel egyre inkább elvárt a rendszerezett áttekintő közlemények készítése esetében is. Az ajánlá-sok szerint a tanulmány szükségességének és hatásterüle-tének meghatározásától az eredmények értékeléséig a rendszerezett irodalmi áttekintés készítésének minden szakaszában javasolt a felhasználók részvétele oly mó-don, hogy előre meghatározzák, melyik fázisban pontosan mit várnak tőlük [15].…”
Section: Az Eredmények öSszefüggésükben Történő Elhelyezése Gyakorlaunclassified